2016
DOI: 10.18632/oncotarget.6994
|View full text |Cite
|
Sign up to set email alerts
|

Expression of aquaporin1, a water channel protein, in cytoplasm is negatively correlated with prognosis of breast cancer patients

Abstract: Aquaporin1 (AQP1) belongs to a highly conserved family of aquaporin proteins which facilitate water flux across cell membranes. Although emerging evidences indicated the cytoplasm was important for AQP1 localization, the function of AQP1 corresponding to its cytoplasmic distribution has rarely been explored until present. In our clinical study, we reported for the first time that AQP1 was localized dominantly in the cytoplasm of cancer cells of invasive breast cancer patients and cytoplasmic AQP1 was an indepe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
68
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(71 citation statements)
references
References 39 publications
3
68
0
Order By: Relevance
“…Namely, a statistically significant association of AQP‐1 high expression with increased survival was observed with a median OS of 12 months for patients with ≥50% AQP‐1 expression vs a median OS of only 7 months for patients with less than 50% AQP‐1 expression. The relationship between higher levels of AQP‐1 in MM and a better prognosis confirms the results of previous studies, but appears to be in conflict with data reported in other tumours, including breast cancer, melanoma, urothelial carcinoma and pharyngeal squamous cell carcinoma, in which increased levels of AQP1 are associated with a poorer prognosis . These data and the relatively few studies on MM require further validation.…”
Section: Discussionsupporting
confidence: 55%
“…Namely, a statistically significant association of AQP‐1 high expression with increased survival was observed with a median OS of 12 months for patients with ≥50% AQP‐1 expression vs a median OS of only 7 months for patients with less than 50% AQP‐1 expression. The relationship between higher levels of AQP‐1 in MM and a better prognosis confirms the results of previous studies, but appears to be in conflict with data reported in other tumours, including breast cancer, melanoma, urothelial carcinoma and pharyngeal squamous cell carcinoma, in which increased levels of AQP1 are associated with a poorer prognosis . These data and the relatively few studies on MM require further validation.…”
Section: Discussionsupporting
confidence: 55%
“…In other types of malignancy, there has been variability in the significance of AQP1 expression levels associated with survival outcomes and tumor phenotype (15,16,24-27). The association between high AQP1 expression and poor prognosis was demonstrated in numerous types of solid cancer, including lung (15,24), breast (16,25), ovarian (26) and cutaneous melanoma cancer (27). In accordance with this, the upregulation of AQP1 was associated with aggressive subtypes of brain tumors (28,29) and cervical cancer (30).…”
Section: Discussionsupporting
confidence: 53%
“…Previous studies have demonstrated that certain classes of AQPs were highly expressed in a variety of cancer types and were associated with tumor biological functions (8,(10)(11)(12)(13)(14). Particularly, increased expression levels of AQP1 have been identified in numerous types of human cancer, including lung, brain, breast, cervical, renal and CRC (8,11,(15)(16)(17). Certain previous studies have demonstrated that AQP1 is involved in tumor cell proliferation, invasion, metastasis and angiogenesis, which may contribute to promoting tumor progression (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…AQP1 overexpression has been associated with poor prognoses in breast [32], lung [33,34], colon [35], prostate [36], and pancreatic cancers [18]. In adenoid cystic carcinoma (ACC), Tan et al [37] observed hypomethylation of the promoter region of the AQP1 gene and overexpression of messenger RNA.…”
Section: Discussionmentioning
confidence: 99%